2008
DOI: 10.1210/me.2007-0457
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Receptor Activation in Ovarian Granulosa Cells Promotes Protein Kinase A-Dependent Dephosphorylation of Microtubule-Associated Protein 2D

Abstract: The actions of LH to induce ovulation and luteinization of preovulatory follicles are mediated principally by activation of cAMP-dependent protein kinase (PKA) in granulosa cells. PKA activity is targeted to specific locations in many cells by A kinase-anchoring proteins (AKAPs). We previously showed that FSH induces expression of microtubule-associated protein (MAP) 2D, an 80-kDa AKAP, in rat granulosa cells, and that MAP2D coimmunoprecipitates with PKA-regulatory subunits in these cells. Here we report a rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 78 publications
2
47
1
Order By: Relevance
“…Studies of rat granulosa cells in culture have shown that LH activation of G s leads to the PKA-dependent activation of PPP2 and that PPP2 is associated with the MAP2D A-kinase anchoring protein (Flynn et al, 2008). One possible scenario, although not the only one, is that NPR2 could also be associated with MAP2D, such that it might be dephosphorylated by PPP2 in response to LH-G s -PKA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of rat granulosa cells in culture have shown that LH activation of G s leads to the PKA-dependent activation of PPP2 and that PPP2 is associated with the MAP2D A-kinase anchoring protein (Flynn et al, 2008). One possible scenario, although not the only one, is that NPR2 could also be associated with MAP2D, such that it might be dephosphorylated by PPP2 in response to LH-G s -PKA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…We initially sought to determine whether MAP2D, the majority of which is highly phosphorylated in naive granulosa cells (Flynn et al, 2008), colocalized with the microtubule, microfilament and/or intermediate cytoskeleton in granulosa cells. Untreated fixed granulosa cells appear flattened and fibroblastic with long bundles of phalloidin-stained F-actin (Karlsson et al, 2010).…”
Section: Map2d Colocalizes With the Vimentin Intermediate Filament Anmentioning
confidence: 99%
“…MAP2D is the only MAP2 isoform detected in rat granulosa cells (Salvador et al, 2004). The majority of MAP2D in preovulatory granulosa cells is phosphorylated, based on its migration on SDS-PAGE gels at 80 kDa rather than at 70 kDa with dephosphorylated MAP2D (Flynn et al, 2008). Addition to primary granulosa cells of an ovulatory concentration of luteinizing hormone, mimicked by the luteinizing hormone chorionic gonadotropin receptor agonist human choriogonadotropin (hCG), promotes rapid dephosphorylation of MAP2D on Thr256 and Thr259 in a PKA-dependent manner (Flynn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AKAPs bind GPCRs [11], ACs [12,13], exchange proteins directly activated by cAMP (Epac) [14], phosphodiesterases (PDEs) [15,16], protein kinases (e.g. protein kinases C, D and N) [17], protein phosphatases such as PP1 [18] and PP2B (calcineurin) [19,20] and ion channels and pumps (e.g. L--type Ca 2+ channels, Na + --Ca 2+…”
Section: Introductionmentioning
confidence: 99%